Temperature distribution in a packed-bed of canola seeds with various moisture contents and bulk volumes during radio frequency (RF) heating. (August 2016) - Yu, Daeung; Shrestha, Bijay L.; Baik, Oon-Doo
Abstract : This research investigated temperature distribution in a packed-bed of canola seeds at various moisture contents (5%, 7%, 9%, and 11% wet weight basis) and bulk volumes (small – 196.3 cm 3, medium – 1766 cm 3, and large – 6503 cm 3 ) during RF heating (1.5 kW, 27.12 MHz). The samples were contained in RF-transparent cylindrical and rectangular sample holders. The RF exposure time required to reach a specific temperature decreased with seed moisture content (MC). The hottest spot (80 °C) was detected at the geometric center of the small and large volume canola seeds, but away from the geometric center and towards the edge of the medium volume canola seeds due to the edge effect. The temperature uniformity index values indicated that the most uniform RF heating was observed in the medium volume canola seeds in spite of the edge effect. The highest temperatures occurred between the middle and outer regions of the medium volume canola seeds. RF heating and thermal imaging were used to obtain temperature profiles for 2% agar gels in small, medium and large holders. The temperature profiles for the gels supported the observations made for the canola seeds. Highlights: We investigated temperature distributions in bulk canola seeds during RF heating. Hottest spots were detected at the centers of the small and large volumes of sample. Hottest spot was moved toward the edge from the geometric center of the medium volume. Temperature profiles of agar gel were in good agreement with those of the bulk canola seeds. Medium volume showed more uniform RF heating in spite of edge effect.